ANALYSIS OF CASES OF DEATHS FROM TB IN CHILDREN IN THE KEMEROVO REGION - Елена Николаевна Лукашова; Инна Федоровна Копылова; Дмитрий Александрович Плохих (Мать и дитя в Кузбассе, 2016)
The analysis of 6 cases of deaths from TB in children in the Kemerovo region for 2013-2015. It is shown that death resulted late diagnosis of TB or absence of this diagnosis. Causes of diagnostic errors must be considered unsatisfactory examination of the environment of children in contact with TB patients, lack of vigilance pediatricians General medical network on the possibility of a tuberculous etiology of the disease in children of early age.